Column Chromatography - Martin, Dean F.; Martin, Barbara B. (IntechOpen, 2013)
This book is characterized by three important features. The authors represent an impressive collection of international workers from Brazil, China, Egypt, Poland, Turkey, and the United States. The majority of the chapters reflect the importance of collaborative efforts in contemporary research. Finally, some chapters are especially useful because of the experimental details that are provided. And it is to be hoped that readers will find that the chapters are both informative and inspirational.